Brain somatostatin receptors are up-regulated in somatostatin-deficient mice - Ramírez, José L. (2002)
The peptide somatostatin (SST) is widely synthesized in the brain and periphery and acts through a family of five receptors (SSTR1-5) to exert numerous effects. A gene product related to SST, cortistatin (CST), also interacts with SSTR1-5. Here we have investigated the regulation of SSTR1-5 and of CST in SST knockout (SSTKO) mice. The five SSTRs were quantitated individually by subtype-selective binding analysis, by immunocytochemistry, and by mRNA measurement and showed, in the brain of SSTKO mice, up-regulation of subtypes 1, 2, 4, and 5, and down-regulation of SSTR3. Peripheral tissues displayed both subtype- and tissue-specific changes in SSTR1-5 mRNA levels of expression. Lack of SST did not up-regulate normal CST expression in brain nor did it induce its expression in the periphery. SST-like immunoreactivity, however, was induced in the proximal midgut in SSTKO animals, suggesting intestinal expression of a novel SST-like gene.